التقاليد الإسلامية الإقليمية بإندونيسيا أفكار صالح دارات و أحمد دحلان و هاشم أشعري (State Islamic University (UIN) of Sunan Ampel Surabaya, 2013)
This paper deals with Saleh Darat’s particularity of Islamic orthodoxy who advocated the purification of Sufism from any un-Islamic contaminations. Saleh Darat is a Javanese Muslim scholar born in Semarang, Central Java, but trained in Makkah, Saudi Arabia, to master classical knowledge of Islam. He is very particular at his time, known as an ardent advocate for Sufism on the one hand, and very critical towards the local Javanese Islamic tradition on the other hand. This specific standpoint has influenced his two students; Hasyim Asy’ari and Ahmad Dahlan. Interestingly, the influence has come with relatively different attitudes and beliefs. Despite his criticism, Hasyim Asy’ari who was later known as a founder of traditionalist Nahdlatul Ulama (NU) still accepted and even acknowledged the tradition as a part of Islam. Meanwhile, from modern persuasion of Muhammadiyah, Ahmad Dahlan’s criticism results from his belief that the tradition is bid‘ah (innovation) and khurafah (superstition).